EVALUASI PROGRAM P5 MENGGUNAKAN MODEL CIPP (CONTEXT, INPUT, PROCESS, AND PRODUCT) BERBASIS MANAJEMEN KELAS DI SD NEGERI KLERO 01 - Rinda Amalia Apprilliani; Herry Sanoto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character education is an important part of the learning process for students. It helps to build good values based on Pancasila, so that students can grow not only in academics but also become strong in facing life challenges. This study aims to evaluate how the P5 (Pancasila Student Profile Strengthening Project) program is carried out at SD Negeri Klero 01. The research uses a qualitative descriptive method with the CIPP model (Context, Input, Process, and Product). The participants in this research include the school principal, fifth grade teacher, and fifth grade students who have joined the P5 program. Data were collected through interviews, classroom observations, and document analysis. The results show that: (1) in the context aspect, the program helps strengthen student character and gives real-life learning experiences; (2) in the input aspect, the school has enough teachers and facilities, even though there are still some shortages; (3) in the process aspect, the program runs as planned; and (4) in the product aspect, there are positive changes in student character and the program continues to be implemented. Cooperation between the school and outside parties is needed to make the program more effective